2020
DOI: 10.1161/atvbaha.119.313832
|View full text |Cite
|
Sign up to set email alerts
|

Statins Disrupt Macrophage Rac1 Regulation Leading to Increased Atherosclerotic Plaque Calcification

Abstract: Objective: Calcification of atherosclerotic plaque is traditionally associated with increased cardiovascular event risk; however, recent studies have found increased calcium density to be associated with more stable disease. 3-hydroxy-3-methylglutaryl coenzymeA reductase inhibitors or statins reduce cardiovascular events. Invasive clinical studies have found that statins alter both the lipid and calcium composition of plaque but the molecular mechanisms of statin-mediated effects on plaque calcium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 77 publications
6
50
0
1
Order By: Relevance
“…Two included studies reported an inverse association, which is in tune with recent theory that statins stabilize plaques by promoting calcification while lowering LDL cholesterol (1); another two reported no association, which is consistent to previous findings from clinical data (5,35,36). Healy et al (37) in a recent article demonstrated that statins, by inhibiting mevalonate synthesis, inhibited downstream cholesterol synthesis and activated downstream Rac1-IL-1β signaling axis. This activation led to a procalcific effect in animal models.…”
Section: Miyoshi Et Alsupporting
confidence: 81%
“…Two included studies reported an inverse association, which is in tune with recent theory that statins stabilize plaques by promoting calcification while lowering LDL cholesterol (1); another two reported no association, which is consistent to previous findings from clinical data (5,35,36). Healy et al (37) in a recent article demonstrated that statins, by inhibiting mevalonate synthesis, inhibited downstream cholesterol synthesis and activated downstream Rac1-IL-1β signaling axis. This activation led to a procalcific effect in animal models.…”
Section: Miyoshi Et Alsupporting
confidence: 81%
“…The authors suggest that this is due to increased activation of unprenylated Rac1 (i.e., generation of the GTP-bound form of the GTPase) and that effector interactions involved in innate immunity are enhanced. This would presumably also apply to statins and recent findings confirm that disruption of Rac1 regulation via statins leads to increased atherosclerotic plaque calcification (47). However, these effects would not be induced by the modes of inhibition used in the present study, thus avoiding the potential negative effects of statins.…”
Section: Discussionsupporting
confidence: 58%
“…Recently, Abigail et al found that although statins have been widely developed as hypolipidemic drugs, they can promote atherosclerotic calcification by relieving the inhibitory effect of RhoGDI (Rho GDP-dissociation inhibitor) on the Rac1-IL-1bsignaling axis in macrophages. Supplementing the isoprenaline precursor can offset the pro-calcified effects of statins to a certain extent (Healy et al, 2020). The increase in calcium deposition caused by statins may be associated with plaque stability.…”
Section: Functional Substances Secreted By Macrophagesmentioning
confidence: 99%